El mito de Fedra en la literatura caballeresca: relectura de un paradigma mitológico femenino en el Flortir (1554) de Mambrino Roseo da Fabriano - Federica Zoppi (Atalaya)
The study is meant to analyze the rewritings of the myth of Fedra in the chivalrous genre, with special attention to Flortir (1554), an Italian chivalric book related to the Spanish tradition, composed by Mambrino Roseo da Fabriano, translator and continuator of the main Spanish chivalrous cycles in Italy. The main focus of the essay will be the female figures and the different models of behaviour that they represent in the different works of the chivalric corpus (with special attention to Tristán de Leonís, Demanda del Santo Grial, Oliveros de Castilla y Tirant lo Blanch, where we can find rewritings of the myth of Phaedra). The purpose will be to consider the elaboration of the classic archetype as a characterizing motif of the genre. At the same time, the analysis will lead to consider how this classic prototype is reinterpreted in the cultural context of 16th century Italian courts where the Italian novels were born.